Hydromechanical Automatic Transmission - Kucera, Lubos; Lukac, Michal; Jurak, Ladislav; Brumercik, Frantisek (Communications - Scientific letters of the University of Zilina, 2009)
This contribution describes some tests of hydromechanical infinitely variable transmission (IVT) on a test stand. Further, there is described a truck with installed IVT and tests of this IVT at real conditions. There is also shown a control system of the IVT.